Fitness efficacy of vibratory exercise compared to walking in postmenopausal women - Raimundo, Armando (2010)
In this study, we compared the efficacy of 8 months of low-frequency vibration and a walk-based program in health-related fitness. Twenty-seven postmenopausal women were randomly assigned into two groups: whole-body vibration (WBV) group (n = 18) performed three times/week a static exercise on a vibration platform (6 sets of 1-min with 1 min of rest, with a 12.6 Hz of frequency and an amplitude of 3 mm); walk-based program (WP) group (n = 18) performed three times/week a 60-min of walk activity at 70-75% of maximal heart rate. A health-related battery of tests was applied. Maximal unilateral concentric and eccentric isokinetic torque of the knee extensors was recorded by an isokinetic dynamometer. Physical fitness was measured using the following tests: vertical jump test, chair rise test and maximal walking speed test over 4 m. Maximal unilateral isokinetic strength was measured in the knee extensors in concentric actions at 60 and 300 degrees /s, and eccentric action at 60 degrees /s. After 8 months, the WP improved the time spent to walk 4 m (20%) and to perform the chair rise test (12%) compared to the WBV group (P = 0.006, 0.002, respectively). In contrast, the comparison of the changes in vertical jump showed the higher effectiveness of the vibratory exercise in 7% (P = 0.025). None of exercise programs showed change on isokinetic measurements. These results indicate that both programs differed in the main achievements and could be complementary to prevent lower limbs muscle strength decrease as we age [ISRCTN76235671].